Efficacy and safety of camrelizumab in combination with S-1 plus oxaliplatin sequenced by camrelizumab-based maintenance therapy as a first-line treatment for advanced gastric or gastroesophageal junction adenocarcinoma: a retrospective cohort study - Wanren Peng; Fei Zhang; Wenwen Ma; Jie Da; Han‐Qing Yu; Lulu Fan; Zhenya Jia; Jing Xu; Zhidong Gao; Changchun Shao; Guoping Sun (2025)
S-1 plus oxaliplatin (SOX) is a first-line standard-of-care treatment for patients with advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma. Programmed cell death protein 1 (PD-1) inhibitors plus chemotherapy, including SOX have also shown promising outcomes in such patients. This study was performed to evaluate the efficacy and safety of camrelizumab plus SOX sequenced by camrelizumab-based maintenance therapy as a first-line treatment for advanced G/GEJ adenocarcinoma. In total, 31 patients with an age of 18 years or older and newly diagnosed with human epidermal growth factor receptor 2 (HER2)-negative advanced G/GEJ adenocarcinoma who underwent camrelizumab in combination with SOX followed by camrelizumab plus S-1 from February 2020 to December 2023 were enrolled in the study. All patients were regularly followed up every 1-2 months. The primary endpoint of the study was progression-free survival (PFS). And the safety profiles were also assessed. As of December 31, 2023, 25 male and 6 female patients were enrolled. The median follow-up time was 14.6 months. The median PFS time of the patients treated with the combination regimen was 7.3 months [95% confidence interval (CI): 3.0-11.6]. In addition, the median overall survival (OS) time was 13.3 months (95% CI: 10.3-16.4), and the median duration of response (DoR) was 5.0 months (95% CI: 2.0-8.1). Moreover, the objective response rate (ORR) and disease control rate (DCR) were 71.0% and 87.1%, respectively. Further, the most commonly observed grade ≥3 adverse events (AEs) were increased gamma-glutamyltransferase (GGT) (9.7%) and a decreased neutrophil count (6.5%). No treatment-related deaths occurred. First-line treatment with camrelizumab in combination with SOX sequenced by camrelizumab-based maintenance therapy demonstrated favorable outcomes for and was well tolerated by patients with advanced G/GEJ adenocarcinoma. Thus, it might serve as a first-line standard-of-care treatment for such patients. However, prospective randomized studies should be carried out to confirm the findings.